Self-powered ionic piezoelectric double-network hydrogel based on PVA / PDMC / CNC-C as well as preparation method and application of self-powered ionic piezoelectric double-network hydrogel
By using PVA/PDMC/CNC-C dual network hydrogel in flexible sensors, the portability and stability of the sensor is solved, fast response and stable output are achieved, sensor performance and reliability are improved, and sensor performance and reliability are suitable for long-term monitoring. application.
Patent Information
- Application Number
- CN202411240848.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2024-12-31
AI Technical Summary
Existing flexible sensors rely on external power supplies, limiting their portability and battery life, and lack of sensitivity and stability, affecting monitoring effects and user health assessment.
Using an ionic piezoelectric double network hydrogel based on PVA/PDMC/CNC-C, cellulose sulfonate nanocrystals were obtained by hydrolyzing cellulose by sulfuric acid, combining polyvinyl alcohol and acryloyloxyethyl trimethyl ammonium chloride, through Ultrasonic mixing and freeze-thaw cycles form a dual network structure for manufacturing self-powered flexible sensors.
It realizes fast response, accurate identification and stable signal output, improves the performance and reliability of the sensor, has excellent mechanical performance and self-powering capabilities, and is suitable for long-term continuous monitoring applications.
Smart Images

Figure CN119219851A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of polymer material science and flexible sensor technology, and specifically relates to a self-powered ionic piezoelectric double network hydrogel based on PVA / PDMC / CNC-C, a preparation method thereof, and an application in a flexible sensor. Background Art
[0002] With the rapid development of science and technology, especially in the wide application of wearable devices, smart medical care, sports tracking and other high-tech fields, flexible sensors have attracted much attention due to their unique performance advantages. Such sensors can fit closely to human skin and sense changes in external stress to cause changes in the internal resistance or capacitance of the sensor, thereby achieving real-time monitoring of human physiological status information. However, despite the significant progress in the technology of flexible sensors, their development is still restricted by some key factors.
[0003] First of all, most existing flexible sensors rely on external power supply, which is one of the important factors restricting their portability and endurance. The external power supply not only increases the overall weight and volume of the device, limiting its application in a small space, but may also lead to frequent battery replacement and increased usage costs, causing inconvenience to users. In addition, for application scenarios that require long-term continuous monitoring, such as sports health monitoring, remote medical monitoring, etc., the external power supply may also cause the device to run out of power during use, thereby affecting the continuity and accuracy of monitoring.
[0004] Secondly, existing flexible sensors also have certain deficiencies in sensitivity and stability. Insufficient sensitivity may cause the sensor to fail to accurately capture tiny physiological change signals, while insufficient stability may lead to large signal fluctuations and poor data reliability. These problems not only affect the monitoring effect of the sensor, but may also mislead the user's health assessment and treatment decision.
[0005] In order to overcome the above shortcomings, researchers have been exploring new materials and technical solutions to improve the performance of flexible sensors. Among them, self-powered flexible sensors have attracted much attention as an innovative technical direction. Self-powered sensors collect mechanical energy, thermal energy, etc. in the environment and convert them into electrical energy to drive the sensor to work. No external power supply is required, thus solving the problems of portability and endurance. However, achieving high performance, high sensitivity and long-term stable self-powered sensing functions is still a huge challenge. Summary of the invention
[0006] The present invention provides a method for preparing an ionic piezoelectric PVA / PDMC / CNC-C double network hydrogel suitable for a flexible sensor. The flexible sensor prepared based on the hydrogel has excellent response time, accurate signal recognition and stable output performance.
[0007] In order to achieve the above-mentioned invention object, the present invention adopts the following technical scheme: A method for preparing an ionic piezoelectric PVA / PDMC / CNC-C double network hydrogel suitable for a flexible sensor, the method comprising the following steps: (1) Hydrolyzing cellulose with sulfuric acid to obtain cellulose sulfonate nanocrystals CNC-C; (2) After completely dissolving the polyvinyl alcohol (PVA) powder in deionized water, acryloyloxyethyl trimethyl ammonium chloride (DMC) monomer and cellulose sulfonate nanocrystals (CNC-C) were added to the polyvinyl alcohol solution and fully mixed by ultrasonication to obtain a PVA / DMC / CNC-C mixed solution; (3) N,N-methylenebisacrylamide MBA is used as a crosslinker and ammonium persulfate APS is used as an initiator to be added to the mixed solution in step (2), and a polyacryloxyethyltrimethylammonium chloride PDMC network is obtained by thermal initiation. The obtained sample is then placed in a refrigerator. After several freeze-thaw cycles, a PVA / PDMC / CNC-C double network hydrogel is finally obtained.
[0008] In step (1), the method for preparing cellulose sulfonate nanocrystals is: Using filter paper as raw material, sulfuric acid is used to hydrolyze cellulose under heating in a water bath to destroy its amorphous region and release the crystalline region. After several cycles of centrifugation, a cellulose sulfonate nanocrystal suspension is obtained. At this time, the solution pH is about 2 and the solid content of the suspension is 4wt%~12wt%.
[0009] In step (2), the mass ratio of PVA to DMC in the PVA / DMC / CNC-C mixed solution is (1-3): (1-3), and the amount of CNC-C added is (1%~4%).
[0010] In step (3), the amount of cross-linking agent added is 0.2wt%~0.3wt%, and the amount of initiator added is 0.5wt%~1wt%.
[0011] An ionic piezoelectric PVA / PDMC / CNC-C double network hydrogel prepared by the above preparation method.
[0012] An application of the ionic piezoelectric PVA / PDMC / CNC-C double network hydrogel in the field of self-powered flexible sensing.
[0013] The above-mentioned ionic piezoelectric PVA / PDMC / CNC-C double network hydrogel is used to manufacture ionic piezoelectric self-powered sensors.
[0014] The specific manufacturing method for manufacturing the ionic piezoelectric self-powered sensor is: The conductive film ITO-PET is used as the electrode, and is laminated on the upper and lower layers of the PVA / PDMC / CNC-C double network hydrogel to form a sandwich structure. Then, wires are led out from the two layers of electrodes and packaged using a biaxially oriented polypropylene film BOPP to obtain a self-powered flexible sensor.
[0015] The beneficial effects of the present invention are: The present invention provides an ionic piezoelectric PVA / PDMC / CNC-C double network hydrogel suitable for flexible sensors, which can achieve rapid response, accurate recognition, and stable output for detecting human motion information. The hydrogel material of the present invention comprises polyvinyl alcohol (PVA), acryloyloxyethyltrimethylammonium chloride (DMC), and cellulose sulfonate nanocrystals (CNC-C). The ionic piezoelectric double network hydrogel is formed through different proportions and ingenious design, and has excellent response time and stable output performance.
[0016] (1) Rapid response and accurate identification: The dual-network hydrogel of the present invention achieves rapid response and accurate identification of human motion information through carefully designed material ratios and structures. This feature ensures the accuracy and timeliness of the sensor in real-time monitoring of human activities, which is of great significance in the fields of sports health monitoring, rehabilitation training, etc.
[0017] (2) Stable output performance: The ionic piezoelectric effect and optimized three-dimensional network structure inside the hydrogel enable the sensor to maintain stable signal output during continuous use, avoiding data errors caused by signal fluctuations or attenuation and improving the reliability of monitoring results.
[0018] (3) Excellent mechanical properties: The PVA / PDMC / CNC-C double network hydrogel combines the flexibility of polyvinyl alcohol (PVA) and the rigidity of polyacryloyloxyethyltrimethylammonium chloride (PDMC), and its mechanical properties are further enhanced by freeze-thaw cycles. The hydrogel can withstand large strains without breaking, ensuring durability and stability in practical applications.
[0019] (4) Self-powered capability: By utilizing the ionic piezoelectric effect of hydrogel, the present invention constructs a self-powered flexible sensor. This sensor can work without an external power supply, greatly simplifies the device structure, improves portability and endurance, and is particularly suitable for application scenarios that require long-term continuous monitoring.
[0020] (4) Broad application prospects: Since the dual-network hydrogel of the present invention has excellent characteristics such as rapid response, accurate recognition, stable output and self-power supply, it is very suitable for application in the field of flexible sensors. Whether in the fields of wearable devices, smart medical care, or sports tracking, the hydrogel can demonstrate its unique advantages and promote technological progress and product innovation in related fields.
[0021] In summary, the PVA / PDMC / CNC-C dual-network hydrogel technology proposed in the present invention has significant beneficial effects in the field of flexible sensors, which not only improves the performance and reliability of sensors, but also promotes the development and application of self-powered sensing technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is the AFM image of the cellulose sulfonate nanocrystals prepared in Example 3.
[0023] Figure 2 This is the SEM image of the PVA / PDMC / CNC-C double network gel prepared in Example 3.
[0024] Figure 3 This is the mechanical properties diagram of the PVA / PDMC / CNC-C double network gel prepared in Example 3.
[0025] Figure 4 This is a performance diagram of the PVA / PDMC / CNC-C double network gel prepared in Example 3 and applied to flexible sensors. DETAILED DESCRIPTION
[0026] The following examples are given to illustrate the present invention in more detail. It is necessary to point out that the following examples cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by technical personnel skilled in the art to the above-mentioned invention contents to the present invention still fall within the scope of protection of the present invention.
[0027] The present invention is further described in detail below in conjunction with the accompanying drawings: The present invention provides a method for preparing an ionic piezoelectric PVA / PDMC / CNC-C double network hydrogel suitable for a flexible sensor, comprising the following steps: Weigh 3g~4g of filter paper, cut it into 0.5cm wide strips, immerse it in deionized water for 4~5 hours, prepare 60wt%~70wt% sulfuric acid solution, measure 30mL~50mL and pour it into a three-necked flask, heat it in a water bath to maintain 60℃~70℃, add the filter paper strips, adjust the magnetic stirring speed to 600rpm~800rpm, maintain the hydrolysis reaction for 20min~30min, add ice deionized water to quench the reaction, and obtain cellulose sulfonate nanocrystals (CNC-C) after several centrifugations.
[0028] Weigh 1g~2g of polyvinyl alcohol (PVA) powder, add it to 10mL~20mL of deionized water, heat it in a water bath to 95℃ and keep it for 30min~60min, observe that the polyvinyl alcohol (PVA) is completely dissolved and then cool it to 40℃~50℃, add acryloyloxyethyltrimethylammonium chloride (DMC) solution according to the mass ratio of polyvinyl alcohol (PVA) and acryloyloxyethyltrimethylammonium chloride (DMC) (1-2): (2-4), and then add 1wt%~4wt% of cellulose sulfonate nanocrystals (CNC-C), keep the water bath temperature at 40℃~50℃, and magnetic The stirring speed was adjusted to 150 rpm~250 rpm, and ultrasonic treatment was performed for 5 min~10 min until the solution was completely dispersed, and cross-linking agent N,N-methylenebisacrylamide (MBA) and initiator ammonium persulfate (APS) were added, with 0.25 wt% cross-linking agent and 1% initiator. The mixture was placed in an oven at 60°C~70°C for 40 min~60 min to obtain a polyacryloxyethyltrimethylammonium chloride (PDMC) network, and then placed in a refrigerator at -18°C~-20°C and subjected to 3~4 freeze-thaw cycles to obtain PVA / PDMC / CNC-double network hydrogel.
[0029] Example 1 Weigh 3 g of filter paper and cut it into 0.5 cm wide strips. Prepare a 60 wt% sulfuric acid solution, measure 30 mL and pour it into a three-necked flask. Heat it in a water bath to maintain 60 °C, add the filter paper strips, adjust the magnetic stirring speed to 600 rpm, maintain the hydrolysis reaction for 25 min, add ice deionized water to quench the reaction, and obtain cellulose sulfonate nanocrystals (CNC-C) after 3 centrifugations.
[0030] Weigh 1.5 g of polyvinyl alcohol (PVA) powder and add it into 10 mL of deionized water and stir slowly. Heat it in a water bath to 95 °C and keep it for 40 min until it is completely dissolved. Cool the solution to 40 °C, add 1.5 g of acryloyloxyethyltrimethylammonium chloride (DMC) and 1 wt% of cellulose sulfonate nanocrystals (CNC-C), and treat it with ice bath ultrasound for 15 min. After stirring and mixing evenly, put it into a 60 °C oven to initiate polymerization to obtain the first layer of network, and then freeze-thaw cycles for 3 times to obtain PVA / PDMC / CNC-double network hydrogel.
[0031] Example 2 Weigh 3 g of filter paper and cut it into 0.5 cm wide strips. Prepare a 65 wt% sulfuric acid solution, measure 30 mL and pour it into a three-necked flask. Heat it in a water bath to maintain 65 °C, add the filter paper strips, adjust the magnetic stirring speed to 600 rpm, maintain the hydrolysis reaction for 20 min, add ice deionized water to quench the reaction, and obtain cellulose sulfonate nanocrystals (CNC-C) after 3 centrifugations.
[0032] Weigh 1.5 g of polyvinyl alcohol (PVA) powder and add it into 10 mL of deionized water and stir slowly. Heat it in a water bath to 95 °C and keep it for 40 min until it is completely dissolved. Cool the solution to 40 °C, add 1.5 g of acryloyloxyethyltrimethylammonium chloride (DMC) and 1 wt% of cellulose sulfonate nanocrystals (CNC-C), and treat it with ice bath ultrasound for 15 min. After stirring and mixing evenly, put it into a 60 °C oven to initiate polymerization to obtain the first layer of network, and then freeze-thaw cycles for 3 times to obtain PVA / PDMC / CNC-double network hydrogel.
[0033] Example 3 Weigh 3 g of filter paper and cut it into 0.5 cm wide strips. Prepare a 65 wt% sulfuric acid solution, measure 30 mL and pour it into a three-necked flask. Heat it in a water bath to maintain 65 °C, add the filter paper strips, adjust the magnetic stirring speed to 600 rpm, maintain the hydrolysis reaction for 20 min, add ice deionized water to quench the reaction, and obtain cellulose sulfonate nanocrystals (CNC-C) after 3 centrifugations.
[0034] Weigh 1.5 g of polyvinyl alcohol (PVA) powder and add it into 10 mL of deionized water and stir slowly. Heat it to 95 °C in a water bath and keep it until it is completely dissolved. Cool the solution to 40 °C, add 2 g of acryloyloxyethyltrimethylammonium chloride (DMC) and 2 wt% of cellulose sulfonate nanocrystals (CNC-C), and treat it with ice bath ultrasound for 15 min. After stirring and mixing evenly, put it into a 60 °C oven to initiate polymerization to obtain the first layer of network, and then freeze-thaw cycles for 3 times to obtain PVA / PDMC / CNC-double network hydrogel.
[0035] Example 4 Weigh 4 g of filter paper and cut it into 0.5 cm wide strips. Prepare a 60 wt% sulfuric acid solution, measure 40 mL and pour it into a three-necked flask. Heat in a water bath to maintain 65 °C, add the filter paper strips, adjust the magnetic stirring speed to 600 rpm, maintain the hydrolysis reaction for 25 min, add ice deionized water to quench the reaction, and obtain cellulose sulfonate nanocrystals (CNC-C) after 3 centrifugations.
[0036] Weigh 1.5 g of polyvinyl alcohol (PVA) powder and add it into 10 mL of deionized water and stir slowly. Heat it to 95 °C in a water bath and keep it until it is completely dissolved. Cool the solution to 40 °C, add 3 g of acryloyloxyethyltrimethylammonium chloride (DMC) and 2 wt% of cellulose sulfonate nanocrystals (CNC-C), and use ice bath ultrasonic treatment for 15 min. After stirring and mixing evenly, put it into a 60 °C oven to initiate polymerization to obtain the first layer of network, and then freeze-thaw cycles for 3 times to obtain PVA / PDMC / CNC-double network hydrogel.
[0037] Example 5 Weigh 4 g of filter paper and cut it into 0.5 cm wide strips. Prepare a 65 wt% sulfuric acid solution, measure 40 mL and pour it into a three-necked flask. Heat it in a water bath to maintain 70 °C, add the filter paper strips, adjust the magnetic stirring speed to 600 rpm, maintain the hydrolysis reaction for 20 min, add ice deionized water to quench the reaction, and obtain cellulose sulfonate nanocrystals (CNC-C) after 3 centrifugations.
[0038] Weigh 1.5 g of polyvinyl alcohol (PVA) powder and add it into 10 mL of deionized water and stir slowly. Heat it to 95 °C in a water bath and keep it until it is completely dissolved. Cool the solution to 40 °C, add 3 g of acryloyloxyethyltrimethylammonium chloride (DMC) and 3 wt% of cellulose sulfonate nanocrystals (CNC-C), and treat it with ice bath ultrasound for 15 min. After stirring and mixing evenly, put it into a 60 °C oven to initiate polymerization to obtain the first layer of network, and then freeze-thaw cycles for 3 times to obtain PVA / PDMC / CNC-double network hydrogel.
[0039] The present invention will be further described below in conjunction with the accompanying drawings.
[0040] Figure 1 The atomic force microscope (AFM) image of the cellulose sulfonate nanocrystal (CNC-C) prepared in Example 3 is shown. The image clearly shows the rod-like structure of the cellulose nanocrystal, and this unique structure provides an effective channel for ion migration in the hydrogel, which plays a key role in improving the ionic piezoelectric properties of the hydrogel.
[0041] Figure 2 This is a scanning electron microscope (SEM) image of the PVA / PDMC / CNC-C double network hydrogel prepared in Example 3. The image intuitively shows the three-dimensional network hole structure of the hydrogel. This structural feature verifies that the prepared material is indeed in the form of a hydrogel, and this network structure helps to enhance the mechanical properties of the hydrogel and promote the transport of ions inside the gel.
[0042] Figure 3 The mechanical properties diagram of the PVA / PDMC / CNC-C double network hydrogel prepared in Example 3 is presented. The figure shows in detail the performance of the hydrogel in the tensile test through the stress-strain curve, where the maximum stress is close to 1.47MPa and the maximum strain can reach 475%. These data fully prove that the hydrogel material prepared by the present invention has excellent mechanical properties and can fully meet the needs of flexible sensors in daily strain monitoring.
[0043] Figure 4Schematic diagram of the performance of the PVA / PDMC / CNC-C dual network hydrogel prepared in Example 3 applied to flexible sensors. The figure is divided into two parts: Figure A shows the signal output of the hydrogel sensor when detecting the bending of the human elbow, proving that the hydrogel sensor has a stable detection capability for complex human body movements; Figure B shows the output response time of the hydrogel sensor, further verifying the rapid response characteristics of the PVA / PDMC / CNC-C dual network hydrogel when applied to flexible sensors.
[0044] In summary, the present invention uses polyacryloyloxyethyl trimethyl ammonium chloride (PDMC) as the first network, freeze-thaw cycled polyvinyl alcohol (PVA) as the second network, and adds sulfuric acid-modified cellulose nanocrystals (CNC-C) to jointly construct a three-dimensional hydrogel network. Among them, the freeze-thaw cycled polyvinyl alcohol (PVA) network and the double network constructed with polyacryloyloxyethyl trimethyl ammonium chloride (PDMC) provide good mechanical properties for the gel. The crystalline regions in sulfuric acid-modified cellulose nanocrystals (CNC-C) and freeze-thaw cycled polyvinyl alcohol (PVA) provide ion channels. In addition, the anionic and cationic groups in acryloyloxyethyl trimethyl ammonium chloride (DMC) and cellulose sulfonate nanocrystals (CNC-C) provide ion adsorption sites inside the gel. These clever designs optimize the piezoelectric output of the gel and improve the gel performance. The specific method is as follows: polyvinyl alcohol (PVA) powder is dissolved in water to obtain a polyvinyl alcohol (PVA) solution, and then acryloyloxyethyltrimethylammonium chloride (DMC) monomer is fully mixed with the polyvinyl alcohol (PVA) solution, and an appropriate proportion of cellulose sulfonate nanocrystals (CNC-C) is added, and the first layer of network polyacryloyloxyethyltrimethylammonium chloride (PDMC) is polymerized by thermal initiation, and then the PVA / PDMC / CNC-C double network hydrogel is obtained by cyclic freeze-thaw method.
[0045] The present invention has good ionic piezoelectric properties and is suitable for flexible sensors, which have fast, accurate and stable response and recognition capabilities. The present invention gives the hydrogel excellent self-powered sensing performance. The hydrogel material has mechanical properties comparable to human skin and responds quickly to external stress. The self-powered flexible sensor prepared thereby has stable, accurate and lasting strain sensing properties.
Claims
1. A method for preparing an ionic piezoelectric PVA / PDMC / CNC-C double network hydrogel suitable for flexible sensors, characterized in that: The method The following steps are involved: The cellulose was hydrolyzed with sulfuric acid to obtain cellulose sulfonate nanocrystals CNC-C; After completely dissolving polyvinyl alcohol (PVA) powder in deionized water, acryloyloxyethyl trimethyl ammonium chloride (DMC) monomer and cellulose sulfonate nanocrystals (CNC-C) were added to the polyvinyl alcohol solution and fully mixed by ultrasonication to obtain a PVA / DMC / CNC-C mixed solution. N,N-methylenebisacrylamide MBA is used as a crosslinker and ammonium persulfate APS is used as an initiator to be added to the mixed solution in step (2), and a polyacryloxyethyltrimethylammonium chloride PDMC network is obtained by thermal initiation. The obtained sample is then placed in a refrigerator, and after several freeze-thaw cycles, a PVA / PDMC / CNC-C double network hydrogel is finally obtained.
2. The method for preparing the ionic piezoelectric PVA / PDMC / CNC-C double network hydrogel according to claim 1, characterized in that: In step (1), the method for preparing cellulose sulfonate nanocrystals is: Using filter paper as raw material, sulfuric acid is used to hydrolyze cellulose under heating in a water bath to destroy its amorphous region and release the crystalline region. After several cycles of centrifugation, a cellulose sulfonate nanocrystal suspension is obtained. At this time, the pH of the solution is about 2, and the solid content of the suspension is 4 wt%~12 wt%.
3. The method for preparing the ionic piezoelectric PVA / PDMC / CNC-C double network hydrogel according to claim 1, characterized in that: In step (2), the mass ratio of PVA to DMC in the PVA / DMC / CNC-C mixed solution is (1-3): (1-3), and the amount of CNC-C added is (1%~4%).
4. The method for preparing the ionic piezoelectric PVA / PDMC / CNC-C double network hydrogel according to claim 1, characterized in that: In step (3), the amount of cross-linking agent added is 0.2 wt%~0.3 wt%, and the amount of initiator added is 0.5 wt%~1 wt%.
5. An ionic piezoelectric PVA / PDMC / CNC-C double network hydrogel prepared by the preparation method as claimed in claim 1.
6. An application of the ionic piezoelectric PVA / PDMC / CNC-C double network hydrogel as claimed in claim 5 in the field of self-powered flexible sensing.
7. The use of the ionic piezoelectric PVA / PDMC / CNC-C double network hydrogel according to claim 6, characterized in that: Used to manufacture ion piezoelectric self-powered sensors.
8. The use of the ionic piezoelectric PVA / PDMC / CNC-C double network hydrogel according to claim 7, characterized in that: The specific manufacturing method is: The conductive film ITO-PET is used as the electrode, and is laminated on the upper and lower layers of the PVA / PDMC / CNC-C double network hydrogel to form a sandwich structure. Then, wires are led out from the two layers of electrodes and packaged using a biaxially oriented polypropylene film BOPP to obtain a self-powered flexible sensor.
Citation Information
Patent Citations
Preparation method of quaternary ammonium salt polyvinyl alcohol-cellulose-graphene oxide composite membrane
CN107446153A
Physical hydrogel with low friction and adjustable modulus as well as preparation method and application of physical hydrogel
CN114507408A
Flexible waterproof cellulose liquid crystal membrane and preparation method thereof
CN115895044A
Double-network PVA-based self-lubricating hydrogel and preparation method thereof
CN118063679A
Preparation method and application of cellulose nanocrystal tough hydrogel
CN118307809A
